Tracking protein function with sodium multi quantum spectroscopy in a 3D-tissue culture based on microcavity arrays - Neubauer, Andreas; Hu, Ruomin; Malzacher, Matthias; Chacón-Caldera, Jorge; Schad, Lothar R. (Scientific reports, 2017)
The aim of this study was to observe the effects of strophanthin induced inhibition of the Na-/K-ATPase in liver cells using a magnetic resonance (MR) compatible bioreactor. A microcavity array with a high density three-dimensional cell culture served as a functional magnetic resonance imaging (MRI) phantom for sodium multi quantum (MQ) spectroscopy. Direct contrast enhanced (DCE) MRI revealed the homogenous distribution of biochemical substances inside the bioreactor. NMR experiments using advanced bioreactors have advantages with respect to having full control over a variety of physiological parameters such as temperature, gas composition and fluid flow. Simultaneous detection of single quantum (SQ) and triple quantum (TQ) MR signals improves accuracy and was achieved by application of a pulse sequence with a time proportional phase increment (TQTPPI). The time course of the Na-/K-ATPase inhibition in the cell culture was demonstrated by the corresponding alterations of sodium TQ/SQ MR signals.